PENGARUH PENGGUNAAN MODEL DISCOVERY LEARNING TERHADAP KETERAMPILAN MENULIS KARANGAN ARGUMENTASI - Elvira, Elvira; Abdurahman, Abdurahman; Ratna, Ellya (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACT There are three purposes of this research. First, to describe of writing argumentative paragraph without using discovery learning. Second, to describe of writing argumentative paragraph by using discovery learning. Third, to describe the effect of the first grade students in writing argumentative paragraph by using discovery learning.Based on the analysis of the data, the researcher concluded that, first writing argumentative paragraph without using discovery learning was classified into (C) with averange 63,26. Second, writing argumentative paragraph by using discovery learning was classified into (B) with averange 78,52. Third, using discovery learning give significantly effect in writing argumentative paragraph. Kata Kunci: pengaruh, discovery learning, karangan argumentasi